ANALYSIS ON THE VARIANCE OF RAW MATERIAL AND DIRECT LABOR COST TOWARD STANDARD COST TO INCREASE THE PROFIT OF OUTFIX_OUTFIT (A READY-MADE GARMENT COMPANY IN MALANG) - Novadilla, Lisa (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research is based on the fact that business competition has become more complex. Companies are trying to survive in their business. One of the strategies that can be taken is controllingproduction cost for efficiency. Standard cost is the cost incurredto produce one unit of product. It is determined at the beginning of the period. Standard cost becomes a benchmark for productioncost control to achieve production cost efficiency.The objectives of this research are (1) to identify the control ofraw material cost and direct labor cost and (2) to describe andanalyze the applied standard cost. The steps of data analysis are (1) determining the standard cost of raw materials and direct labor,(2) comparing standard production cost and actual production cost, and (3) analyzing the difference between standard production cost and actual production cost, if any. Â Â  Keywords: Standard Cost, Production Cost